Does Corporate Governance Affect Dividends? Case Study in Indonesia Stock Exchange and Malaysia Stock Exchange - Budy Wijaya Hermawan; Werner Ria Murhadi; Endang Ernawati (Journal of Entrepreneurship and Business, 2022)
Abstract – This study aims to analyze the effect of good corporate governance such as the number of commissioners, the number of commissioner meetings, the number of female commissioners, the independent commissioners on the dividend payout ratio in manufacturing companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange. Malaysia was chosen because has a dividend payout rate close to Indonesia. This research uses a quantitative approach using multiple linear regression methods. The research used objects of 435 observations on the Indonesia Stock Exchange and 530 observations on the Malaysia Stock Exchange. The independent variables used are independent commissioners, board of commissioners meetings, size of commissioners, female commissioners. The results of the study using observations on the Indonesia Stock Exchange found that independent commissioners have a significant positive effect while the rest have an insignificant effect on the dividend payout ratio. Meanwhile, the results of the study using observations on the Bursa Malaysia found that the size of the commissioners and board of commissioners' meetings had a significant negative effect on the dividend payout ratio. Meanwhile, independent commissioners and female commissioners have a significant positive effect on the dividend payout ratio.